2019
DOI: 10.1016/j.ebiom.2019.07.025
|View full text |Cite
|
Sign up to set email alerts
|

Across continents and demographics, unpredictable maternal signals are associated with children's cognitive function

Abstract: Background Early life experiences have persisting influence on brain function throughout life. Maternal signals constitute a primary source of early life experiences, and their quantity and quality during sensitive developmental periods exert enduring effects on cognitive function and emotional and social behaviors. Here we examined if, in addition to established qualitative dimensions of maternal behavior during her interactions with her infant and child, patterns o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
74
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 48 publications
(87 citation statements)
references
References 50 publications
(71 reference statements)
11
74
2
Order By: Relevance
“…Entropy rate can vary between a minimum value of zero, when a process is perfectly predictable, to a maximum value of 2.807 (the logarithm [base two] of the number of possible transitions [7] of sensory signals at each step), when all possible transitions in this coding scheme are equally likely and maternal signals are most unpredictable. The entropy rates of maternal sensory signals during the 6‐ and 12‐month mother–infant play interactions were correlated ( r = 0.46, p < .01) and consistent with prior research averaged to create a composite measure of unpredictable maternal sensory signals in infancy (Davis et al, 2019).…”
Section: Methodssupporting
confidence: 76%
See 1 more Smart Citation
“…Entropy rate can vary between a minimum value of zero, when a process is perfectly predictable, to a maximum value of 2.807 (the logarithm [base two] of the number of possible transitions [7] of sensory signals at each step), when all possible transitions in this coding scheme are equally likely and maternal signals are most unpredictable. The entropy rates of maternal sensory signals during the 6‐ and 12‐month mother–infant play interactions were correlated ( r = 0.46, p < .01) and consistent with prior research averaged to create a composite measure of unpredictable maternal sensory signals in infancy (Davis et al, 2019).…”
Section: Methodssupporting
confidence: 76%
“…Patterns of sensory signals, and particularly their unpredictability, additionally affect the development of systems involved in memory (Molet et al, 2016) and reward (Bolton, Molet, et al, 2018). Recent cross‐species (rodents and humans) evidence suggests unpredictable maternal sensory signals affect cognitive function, with replication across continents (North America and Europe) (Davis et al, 2017, 2019).…”
Section: Introductionmentioning
confidence: 98%
“…Our results are consistent with previously published findings and further demonstrate that chronic psychosocial stress during pregnancy can affect qualitative aspects of maternal care, resulting in fragmented and unpredictable care patterns. Erratic maternal care patterns have been previously reported in dams subjected to impoverished/limited bedding environment [42][43][44] and have been linked to emotional and cognitive disturbances in rodent and human offspring 42,43,[53][54][55] . We also find psychosocial stressors contribute to the emergence of PPD by interfering with basal and stress-induced peripartum HPA axis adaptations.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to these typical measures of maternal care, we analyzed more qualitative aspects of maternal behavior after CGS exposure, including the degree of fragmentation and unpredictability of maternal signals. Fragmented and unpredictable care patterns seem to reflect poorer maternal care quality and have been associated with maternal pathology [42][43][44][53][54][55] . For CGS dams, the mean duration of licking/grooming bouts was significantly shorter than control dams (t-test, t 32 = 2.709, P = 0.011) ( Fig.…”
Section: Effect Of Chronic Psychosocial Stress During Pregnancy On Mamentioning
confidence: 99%
“…These correlations persisted when typical measures of adversity, including SES and maternal depression, were included in the models. A second study in an ethnically and demographically distinct prospective cohort identified a relationship between unpredictability of environmental signals in infancy and cognitive outcomes 78 .…”
Section: Wwwnaturecom/nrneurolmentioning
confidence: 99%